2020
DOI: 10.7554/elife.60371
|View full text |Cite
|
Sign up to set email alerts
|

CMG helicase disassembly is controlled by replication fork DNA, replisome components and a ubiquitin threshold

Abstract: The eukaryotic replisome assembles around the CMG helicase, which stably associates with DNA replication forks throughout elongation. When replication terminates, CMG is ubiquitylated on its Mcm7 subunit and disassembled by the Cdc48 / p97 ATPase. Until now, the regulation that restricts CMG ubiquitylation to termination was unknown, as was the mechanism of disassembly. By reconstituting these processes with purified budding yeast proteins, we show that ubiquitylation is tightly repressed throughout elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
122
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(146 citation statements)
references
References 66 publications
(150 reference statements)
14
122
1
Order By: Relevance
“…Importantly, CMG unloading at termination sites occurs after the formation of fully ligated DNA products during in vitro replication in X. laevis egg extracts, which suggested that a specific conformational change must occur to promote MCM7 ubiquitylation and p97dependent unfolding and disassembly of the CMG [121]. Consistent with this, in vitro reconstitution with purified budding yeast proteins recently showed that MCM7 ubiquitylation is normally repressed throughout fork elongation by the Y-shaped DNA structure of the replication fork itself, which is removed upon fork convergence and end-product ligation [122]. Efficient fork convergence and termination also necessitate activity of topoisomerase II and the Pif1 and Rrm3 DNA helicases [123].…”
Section: Seckel Syndrome and Other Mpdsmentioning
confidence: 83%
“…Importantly, CMG unloading at termination sites occurs after the formation of fully ligated DNA products during in vitro replication in X. laevis egg extracts, which suggested that a specific conformational change must occur to promote MCM7 ubiquitylation and p97dependent unfolding and disassembly of the CMG [121]. Consistent with this, in vitro reconstitution with purified budding yeast proteins recently showed that MCM7 ubiquitylation is normally repressed throughout fork elongation by the Y-shaped DNA structure of the replication fork itself, which is removed upon fork convergence and end-product ligation [122]. Efficient fork convergence and termination also necessitate activity of topoisomerase II and the Pif1 and Rrm3 DNA helicases [123].…”
Section: Seckel Syndrome and Other Mpdsmentioning
confidence: 83%
“…For instance, the protease DDI2 will cleave the transcription factor NRF1 only when it is modified with long polyUb chains (Dirac-Svejstrup et al, 2020). Similarly, the unfoldase Cdc48/p97-Ufd1-Npl4 has several ubiquitin binding sites and efficiently unfolds Mcm7 only when it is modified with K48 chains containing atleast five ubiquitins (Deegan et al, 2020;Twomey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In higher eukaryotes, CMG unloading is driven by K48-linked polyubiquitylation of the MCM7 subunit by the CRL2 LRR1 E3 ligase (SCF Dia2 in budding yeast) and subsequent extraction by the p97-UFD1-NPL4 complex [26][27][28][29]. Recent studies in yeast and vertebrates indicate that the DNA structure of elongating replication forks sterically blocks the interaction between CMG and CRL2 LRR1 , thereby suppressing CMG ubiquitylation and unloading until fork convergence has occurred [101][102][103]. In the absence of CRL2 LRR1 , TRAIP provides an alternative pathway for ubiquitin-driven CMG unloading during mitosis, which is critical for preserving viability when cells enter mitosis with incompletely replicated DNA [30,103,104].…”
Section: Replication Termination and Cmg Helicase Unloadingmentioning
confidence: 99%